2014
DOI: 10.1128/iai.02546-14
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-Triggered Calcium Mobilization Protects Mice against Bacterial Infection through Extracellular ATP Release

Abstract: Extracellular ATP (eATP), released as a "danger signal" by injured or stressed cells, plays an important role in the regulation of immune responses, but the relationship between ATP release and innate immune responses is still uncertain. In this study, we demonstrated that ATP was released through Toll-like receptor (TLR)-associated signaling in both Escherichia coli-infected mice and lipopolysaccharide (LPS)-or Pam3CSK4-treated macrophages. This ATP release could be blocked completely only by N-ethylmaleimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 29 publications
0
50
0
2
Order By: Relevance
“…For example, ATP can be released via exocytosis 30 min after challenged by bacterial infection, both in vivo and in vitro (25,32). We also found that UDP could be highly released through pannexin channel in 24 h after virus infection.…”
Section: Discussionmentioning
confidence: 56%
“…For example, ATP can be released via exocytosis 30 min after challenged by bacterial infection, both in vivo and in vitro (25,32). We also found that UDP could be highly released through pannexin channel in 24 h after virus infection.…”
Section: Discussionmentioning
confidence: 56%
“…During bacterial infection or tissue damage, ATP is released from the intracellular compartments of both the host and bacterial cells into the extracellular milieu (9, 33, 34). The extracellular ATP, acting as a second signal for canonical NLRP3 inflammasome activation, induces pyroptosis in innate immune cells including macrophages (6).…”
Section: Discussionmentioning
confidence: 99%
“…Given that more internal energy failed to produce more surviving RGCs, we questioned whether supplying extrinsic ATP would confer any benefit for RGC survival. ATP was injected at a relatively high dose (50 mg/kg) [37,38] and a low dose (5 lmol/kg; *2.865 mg/kg) [39]. Intraperitoneal injections did not have a significant effect on RGC survival in either injured or intact eyes (Fig.…”
Section: Neither Systemic Increases In Internal Energy Levels Nor Supmentioning
confidence: 96%